2016
DOI: 10.1002/adsc.201600274
|View full text |Cite
|
Sign up to set email alerts
|

Reagent/Substituent Switching Approach for the Synthesis of Substituted 1,3,4‐Oxadiazole/1,3,4‐Oxadiazoline and 1,2,4‐Triazole Derivatives from N‐Substituted Hydrazides

Abstract: A metal‐free method for the synthesis of substituted 1,3,4‐oxadiazole/1,3,4‐oxadiazoline and 1,2,4‐triazole derivatives from a common starting material via reagent/substituent switching is reported. In the presence of 2‐fluoropyridine/triflic anhydride, 1,3,4‐oxadiazole derivatives were exclusively formed from N′‐tert‐butylhydrazides and 1,3,4‐oxadiazoline derivatives were produced from N‐phenylhydrazides. On the other hand, when using pyridine/triflic anhydride, salts of 1,2,4‐triazoles were the sole products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…Unless otherwise noted. All compounds were characterized by 1 H NMR and 13 C NMR, which are consistent with those reported in the literature.…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…Unless otherwise noted. All compounds were characterized by 1 H NMR and 13 C NMR, which are consistent with those reported in the literature.…”
Section: Methodssupporting
confidence: 78%
“…(Table 1, entry 11). When the temperature was reduced to 80 °C and 100 °C or increased to 120 °C, the yield decreased to 57%, 78%, and 84%, respectively (Table 1, entries [12][13][14]. Considering the influence of cobalt salts, we found that Co(NO 3 ) 2 •6H 2 O is the only effective one (Table 1, entries 1, 15 −17).…”
Section: Scheme 3 Scale-up Experimentsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the imines compounds, especially for alkyl imines, are rather labile substrates for their preparation [ 15 ]. Another approach to the construction of 1,2,4-oxadiazole skeletons is produced by the condensation of amidoximes with a carbonyl compound [ 18 , 19 , 20 , 21 ]. These condensation reactions existed under often harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%